2018
DOI: 10.1002/bem.22125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1.8 GHz radiofrequency field on microstructure and bone metabolism of femur in mice

Abstract: To investigate the effects of 1.8 GHz radiofrequency (RF) field on bone microstructure and metabolism of femur in mice, C57BL/6 mice (male, age 4 weeks) were whole-body exposed or sham exposed to 1.8 GHz RF field. Specific absorption rates of whole body and bone were approximately 2.70 and 1.14 W/kg (6 h/day for 28 days). After exposure, microstructure and morphology of femur were observed by microcomputed tomography (micro-CT), Hematoxylin and Eosin (HE) and Masson staining. Subsequently, bone parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…In this study, the histological results of the OVX group indicated the occurrence of thinning and loss of trabeculae, reduction of cortical thickness, and increase in cortical porosity, which are the characteristics of the pathological process of osteoporosis [Parfitt et al, 1983;Compston et al, 2019]. The pathological changes were alleviated after PEMF or MEL treatments; this result is consistent with the findings of previous studies [Tresguerres et al, 2014;Guo et al, 2018;Liu et al, 2019]. Interestingly, there was an increase in the expression levels of osteogenic proteins (BMP2 and COL1), and a substantial decrease in the number of osteoclasts after PEMF + MEL exposure, suggesting that the negative bone remodeling balance was reversed because of the promotion of osteogenesis and inhibition of bone resorption.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the histological results of the OVX group indicated the occurrence of thinning and loss of trabeculae, reduction of cortical thickness, and increase in cortical porosity, which are the characteristics of the pathological process of osteoporosis [Parfitt et al, 1983;Compston et al, 2019]. The pathological changes were alleviated after PEMF or MEL treatments; this result is consistent with the findings of previous studies [Tresguerres et al, 2014;Guo et al, 2018;Liu et al, 2019]. Interestingly, there was an increase in the expression levels of osteogenic proteins (BMP2 and COL1), and a substantial decrease in the number of osteoclasts after PEMF + MEL exposure, suggesting that the negative bone remodeling balance was reversed because of the promotion of osteogenesis and inhibition of bone resorption.…”
Section: Discussionsupporting
confidence: 91%
“…This is because of the fact that the blood reflects the pathophysiology of the whole body. In the present study, the results showed that electromagnetic radiation from cell phones causes statically significant changes in RBCs, Hb, HCT, MCV, MCHC, PLT, and WBCs levels which are in a good agreement with that reported in other publications [6,15,16]. Exposure to cell phone radiation increases the concentration of peroxynitrite that can interfere with the proper function of cells and damage it.…”
Section: Discussionsupporting
confidence: 93%
“…RF fields, a kind of electromagnetic field at the frequency ranging from 100 kHz to 300 GHz, has gone through phenomenal development and deployment worldwide in recent years [7]. With the rapid expansion of devices generating RF fields, the intensity, time and complexity of exposure to RF fields are increasing, which has triggered widespread concern about the safety of RF exposure.…”
Section: Introductionmentioning
confidence: 99%